Developments in managing severe chronic pain: role of oxycodone–naloxone extended release - Fanelli, Guido (Drug Des Devel Ther, 2015)
Chronic pain is a highly disabling condition, which can significantly reduce patients’ quality of life. Prevalence of moderate and severe chronic pain is high in the general population, and it increases significantly in patients with advanced cancer and older than 65 years. Guidelines for the management of chronic pain recommend opioids for the treatment of moderate-to-severe pain in patients whose pain is not responsive to initial therapies with paracetamol and/or nonsteroidal anti-inflammatory drugs. Despite their analgesic efficacy being well recognized, adverse events can affect daily functioning and patient quality of life. Opioid-induced constipation (OIC) occurs in 40% of opioid-treated patients. Laxatives are the most common drugs used to prevent and treat OIC. Laxatives do not address the underlying mechanisms of OIC; for this reason, they are not really effective in OIC treatment. Naloxone is an opioid receptor antagonist with low systemic bioavailability. When administered orally, naloxone antagonizes the opioid receptors in the gut wall, while its extensive first-pass hepatic metabolism ensures the lack of antagonist influence on the central-mediated analgesic effect of the opioids. A prolonged-release formulation consisting of oxycodone and naloxone in a 2:1 ratio was developed trying to reduce the incidence of OIC maintaining the analgesic effect compared with use of the sole oxycodone. This review includes evidence related to use of oxycodone and naloxone in the long-term management of chronic non-cancer pain and OIC.